2018
DOI: 10.1002/stco.201800018
|View full text |Cite
|
Sign up to set email alerts
|

Use of HSS and VHSS in steel structures in civil and offshore engineering

Abstract: The use of high-strength steels (HSS, 460 < f y ≤ 700 MPa) and particularly very high-strength steels (VHSS, f y > 700 MPa) is limited in steel structures in civil and offshore engineering. This is due to a lack of experience in structures made of these materials and a lack of understanding of the structural performance of HSS and VHSS. The main questions that are unanswered concern the topics of static strength, fracture toughness, fatigue, material (in) homogeneity and manufacturing. With regard to the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…authors reported relatively low fatigue life, which resulted from the formation of imperfections during the welding process [2]. However, the fatigue strength behavior of welded joints is independent of the fatigue behavior of parent material in an as-welded state [3]. Therefore, Berg et al [4] performed research work to improve the fatigue strength on welded joints ultra-high strength steels (UHSS) by hammer peening.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…authors reported relatively low fatigue life, which resulted from the formation of imperfections during the welding process [2]. However, the fatigue strength behavior of welded joints is independent of the fatigue behavior of parent material in an as-welded state [3]. Therefore, Berg et al [4] performed research work to improve the fatigue strength on welded joints ultra-high strength steels (UHSS) by hammer peening.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…1 GBF: Ferrite with primary grain boundary. 2 FS: Ferrite side plate 3. FSA: Ferrite with second aligned phase, upper bainite.…”
mentioning
confidence: 99%
“…While high-strength structural steels are readily available with yield strength even above 1000 MPa and are regulated in standards for steel constructions like Eurocode 3 up to 700 MPa, their use remains limited to day [15]. Although, high-strength steel offers extensive design potential, typical civil and offshore engineering structures are to this day mainly build of S355 steel [16].…”
Section: Experimental Study 31 Materialsmentioning
confidence: 99%
“…The applications of HSS and UHSS are becoming significantly attractive in variety of engineering sectors such as bridge construction [20], building structures [21], offshore [22] etc. With the increasing interest to use HSS/UHSS, rehabilitation and strengthening of struc tures made of such steel grades especially at the welded area becomes vital.…”
Section: Introductionmentioning
confidence: 99%